Differences in macular structure and microvasculature between high myopia and non-high myopia - Chen, Qin; Song, Keyao; Cun, Qing; Yang, Wenyan; Tao, Yijin; Zhong, Hua; Lv, Shitou; Qian, Chaoxu (Frontiers in Medicine, 2025)
PurposeTo investigate the retinal and choroidal morphological and microvascular changes in myopic eyes using optical coherence tomography angiography (OCTA).MethodsIn this retrospective, cross-sectional study, 142 eyes from 84 myopic patients were categorized into two groups based on spherical equivalent (SE): high myopia (HM; SE ≤ −6.0 D, 72 eyes) and non-high myopia (NHM; −6.0 D < SE ≤ −0.5 D, 70 eyes) groups. OCTA-derived parameters, including foveal retinal thickness (RT), choroidal thickness (CT), superficial retinal vessel density (SRVD) and deep retinal vessel density (DRVD), choriocapillaris density (CCD), and foveal avascular zone (FAZ) area and perimeter, were analyzed.ResultsThe mean SE was −10.16 ± 3.55 D in the HM group and −3.86 ± 1.60 D in the NHM group. RT measurements revealed substantial increases in HM eyes, including total foveal (276.4 ± 36.1 μm vs. 250.1 ± 23.3 μm; p < 0.01), parafoveal (348.0 ± 23.0 μm vs. 329.7 ± 20.8 μm; p < 0.01), and perifoveal regions (304.9 ± 25.1 μm vs. 290.6 ± 15.5 μm; p < 0.01). Retinal vascular analysis showed reduced SRVD in the fovea with borderline significance (14.9 ± 7.1% vs. 17.9 ± 7.4%; p = 0.05), while DRVD showed a non-significant reduction (31.4 ± 10.1% vs. 37.8 ± 24.0%; p > 0.05). HM eyes exhibited significant choroidal thinning (169.2 ± 74.0 μm vs. 222.4 ± 70.7 μm; p < 0.01) and decreased CCD (55.7 ± 3.1% vs. 58.0 ± 2.6%; p < 0.01). The FAZ displayed a larger area (0.4 ± 0.4 mm2 vs. 0.3 ± 0.1 mm2; p = 0.07) and perimeter (2.5 ± 1.1 mm vs. 2.1 ± 0.4 mm; p < 0.05) in HM subjects.ConclusionHigh myopia is associated with distinct retinal and choroidal alterations, including increased RT, reduced CT and CCD, and enlarged FAZ, suggesting progressive microvascular and structural remodeling with myopia severity.